Negotiating Authority and Identity: The Political Mobilization of Gaddi Shepherds in Himachal Pradesh (1947–Present) - Thakru, Ram (RESEARCH HUB International Multidisciplinary Research Journal, 2025)
This paper examines the evolving political mobilization of the Gaddi community, one of the prominent transhumant pastoral groups of Himachal Pradesh, from the time of India’s independence in 1947 to the present. It argues that the Gaddi political journey represents a continuous process of negotiation—between state authority, defined largely through forest and revenue bureaucracies, and the community’s own assertion of a distinct hill identity within the democratic order. Historically marginalized under the restrictive forest policies of the colonial regime, the Gaddis’ post-independence experience reflects a gradual shift from localized resistance over grazing rights to organized political participation. The study highlights two major arenas of this transformation. The first is the bureaucratic–ecological conflict, shaped by the tension between customary grazing claims (wazib-ul-arz) and modern conservation frameworks. The second concerns the democratic assertion of identity, wherein the recognition of the Gaddis as a Scheduled Tribe in 1956 became a crucial political resource. This status facilitated the emergence of local leadership, community associations, and a visible presence in state politics, particularly in Chamba and Kangra districts. The paper further argues that the Gaddi political identity has been both inclusive and contested. While the public image of a unified, Shiva-worshipping Gaddi community has served as an effective tool for political representation and reservation benefits, internal divisions—especially between traditional pastoralists and an increasingly educated elite—have complicated this unity. The Gaddi experience thus offers valuable insight into how historically nomadic groups transform ecological struggles into political capital, illustrating broader patterns of tribe–state relations and democratic adaptation in contemporary South Asia.